Organizational cultural factors influencing continuous improvement in Saudi universities - Alotaibi, Mohammed Saeed; McLaughlin, Patrick; Al-Ashaab, Ahmed (IBIMA, 2019)
Continuous Improvement (CI) is described as a culture of sustainable improvements aimed at making organizational processes and systems increasingly efficient. The importance of CI, especially in higher education institutions (HEIs), relies heavily on those institutions’ importance in the success of individuals, organizations and countries as a whole. Despite its importance, there is a lack of sufficient studies on the role of CI in the success of universities in Saudi Arabia. This paper aims to identify the organizational cultural factors (OC) that influence CI efforts within the Saudi HEIs, in order to provide an understanding of the enabling and inhibiting factors of such efforts. This study has adopted a qualitative grounded theory approach, which aims to identify the OC aspects that have an impact on the CI of Saudi HEIs. It identifies eight themes that influence CI implementation in Saudi HEIs, which are: External Engagement, Institutional management, Skills Enhancement, Institutional Strategies, Development & Growth, Obstacles To Success, Ethical Issues and University Infrastructure.
Keywords: Continuous Improvement; Organizational Culture; Saudi Universities